The Legionary Rebellion in the Diplomatic Reports of Ivan Milecz - Radu Florian Bruja (Codrul Cosminului, 2022)
The study of diplomatic records revealed new details concerning the Nazi Reich's satellites in the setting of early 1941 Central Europe. It is well known today that Hitler played a decisive role in the conflict between Ion Antonescu and the Legionary Movement. However, new findings concerning the events in Romania in January 1941 continue to provide conflicting results. This investigation focuses on the reports of Ivan Milecz, the Slovak diplomat accredited in Bucharest, which were not known to previous historians. The problem of sources poses a major challenge to historians in their efforts to reconstruct the past. Although he was not well informed, Milecz managed to relay details about the legionary rebellion in Bucharest. These reports had a double significance for Bratislava. They were not merely information but political suggestions for the top power struggle in Slovakia. Their study contributes to a more complete picture of the nature of the January 1941 events for both Romania and Slovakia.